2012
DOI: 10.1111/j.1460-9568.2012.08180.x
|View full text |Cite
|
Sign up to set email alerts
|

SREB2/GPR85, a schizophrenia risk factor, negatively regulates hippocampal adult neurogenesis and neurogenesis‐dependent learning and memory

Abstract: SREB2/GPR85, a member of the super-conserved receptor expressed in brain (SREB) family, is the most conserved G-protein-coupled receptor in vertebrate evolution. Previous human and mouse genetic studies have indicated a possible link between SREB2 and schizophrenia. SREB2 is robustly expressed in the hippocampal formation, especially in the dentate gyrus, a structure with an established involvement in psychiatric disorders and cognition. However, the function of SREB2 in the hippocampus remains elusive. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…org/; Lewis et al, 2005). Also, the recent demonstration that SREB2 is involved in hippocampal adult neurogenesis (Chen et al, 2012) may be consistent with the notion that SREB2 may not be a risk gene specific to schizophrenia alone. Moreover, there are frequent examples of genetic variation associated with multiple psychiatric phenotypes (Millar et al, 2000).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…org/; Lewis et al, 2005). Also, the recent demonstration that SREB2 is involved in hippocampal adult neurogenesis (Chen et al, 2012) may be consistent with the notion that SREB2 may not be a risk gene specific to schizophrenia alone. Moreover, there are frequent examples of genetic variation associated with multiple psychiatric phenotypes (Millar et al, 2000).…”
Section: Discussionsupporting
confidence: 62%
“…This expression pattern is consistent with the behavioral profile of the SREB2 transgenic mice that show alterations in contextual fear conditioning, ie, the behavioral response to a stressful cage environment, which is mediated by amygdala and hippocampal formation (HF) in rodents. More recently, Chen et al (2012) showed that SREB2 affects adult neurogenesis and neurogenesis-dependent learning in a transgenic mouse model. Given these data, a reasonable prediction is that the function of the amygdalarhippocampal system would be preferentially affected in individuals carrying risk-associated alleles for rs56080411 and rs56039557 as compared with non-carriers, even in normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the protocol used previously (6,36), the apparatus for this behavioral task contained an open field (84 cm long ϫ 42 cm wide ϫ 15 cm high) and two distinct objects measuring between 2.5 and 5 cm at the base and between 5 and 15 cm tall, which were used as stimuli in these tasks. Mice between 8 and 10 weeks of age were used for the behavioral task.…”
Section: Methodsmentioning
confidence: 99%
“…The DISC1 (disrupted-inschizophrenia 1) gene is a key regulator that orchestrates the tempo of functional neuronal integration in the adult mouse brain (4). Other risk genes have also been found to be involved in the regulation of adult hippocampal neurogenesis, such as NPAS3 (neuronal PAS domain protein 3) (5) and SREB2/ GPR85 (G protein-coupled receptor 85) (6).…”
mentioning
confidence: 99%
“…No such changes were noted when comparing single mutants with control mice. Altered exploratory behavior of ACC mice in the Y-maze suggests impaired working memory (32). To study working memory in an independent approach, we tested the mice on an eight-arm radial maze using a win-shift rule (33).…”
Section: Impaired Working Memory In Acc Micementioning
confidence: 99%